2019
DOI: 10.1177/1559325819891043
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Radiography in Monitoring Structural Changes in the Treatment of Spinal Disorders in Chiropractic and Manual Medicine Practice: Evidence and Safety

Abstract: There is substantial evidence for normal relationships between spine and postural parameters, as measured from radiographs of standing patients. Sagittal balance, cervical lordosis, thoracic kyphosis, lumbar lordosis, pelvic tilt, and the more complex understanding of the interrelations between these essential components of normal stance have evolved to where there are known, established thresholds for normalcy. These spinal parameters are reliably measured from X-ray images and serve as goals of care in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 111 publications
(165 reference statements)
0
26
0
4
Order By: Relevance
“…Also, the population groups studied were all similar, mid-aged adults (average ages 39–46 years). Although limited, there is good quality evidence that indicates increasing the lumbar lordosis via extension traction as part of multimodal rehabilitation programs are associated with superior outcomes over ‘standard-care’ treatment programs that do not improve hypolordosis 52 ) . The strength of the RCT designs was accomplished by having randomized comparison groups who received identical treatments less the traction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the population groups studied were all similar, mid-aged adults (average ages 39–46 years). Although limited, there is good quality evidence that indicates increasing the lumbar lordosis via extension traction as part of multimodal rehabilitation programs are associated with superior outcomes over ‘standard-care’ treatment programs that do not improve hypolordosis 52 ) . The strength of the RCT designs was accomplished by having randomized comparison groups who received identical treatments less the traction.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns over radiation exposures during routine spinal X-ray imaging need discussion. Although this topic has been thoroughly discussed elsewhere [57][58][59][60], in brief, patient exposures from spinal X-rays are not harmful. First, the assumption that radiation exposures from low-doses are carcinogenic is false; low-doses of radiation (including X-rays and CT scans) stimulate the adaptive protection systems in the body to "over-repair" any genetic damage done, including DNA double strand breaks by imaging [61].…”
Section: Contraindications To Extension Tractionmentioning
confidence: 99%
“…First, the assumption that radiation exposures from low-doses are carcinogenic is false; low-doses of radiation (including X-rays and CT scans) stimulate the adaptive protection systems in the body to "over-repair" any genetic damage done, including DNA double strand breaks by imaging [61]. Second, because of point one, there is no cumulative effect; therefore, the only relative risk can be considered from a single session of X-rays (i.e., 1-3 mGy) [57,58]. Third, due to point two, the amount of radiation from X-rays of 1-3 mGy is many times lower than the recognized dose threshold for leukemia of 1100 mGy (95% CI: 500-2600 mGy) [57,62] and therefore cannot be carcinogenic.…”
Section: Contraindications To Extension Tractionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also documented that the data from multiple studies has shown less cancers in those occupationally exposed to low-doses of radiation, 39 suggesting low-dose exposures as having a protective effect, and to prevent cancers. 42 As discussed recently, 43 there is actually much evidence not only showing no harm from seemingly large radiation exposures (up to 500-800 mSv), but increased protective effects and less cancers. Calabrese et al for example demonstrated in the early and mid 1900s, many human ills were treated by radiotherapy where patients were exposed to doses ranging from about 30-100 roentgen (∼263-877 mSv), which resulted in success rates of 75-90%.…”
Section: Estimated Theoretical Cumulative Effective Doses Remain Belomentioning
confidence: 94%